Crisis Management of Tohoku; Japan Earthquake and Tsunami, 11 March 2011 - M Zaré; S Ghaychi Afrouz (Tehran University of Medical Sciences, 2012)
The huge earthquake in 11 March 2012 which followed by a destructive tsunami in Japan was largest recorded earthquake in the history. Japan is pioneer in disaster management, especially earthquakes. How this developed country faced this disaster, which had significant worldwide effects? The humanitarian behavior of the Japanese people amazingly wondered the word's media, meanwhile the management of government and authorities showed some deficiencies. The impact of the disaster is followed up after the event and the different impacts are tried to be analyzed in different sectors. The situation one year after Japan 2011 earthquake and Tsunami is overviewed. The reason of Japanese plans failure was the scale of tsunami, having higher waves than what was assumed, especially in the design of the Nuclear Power Plant. Japanese authorities considered economic benefits more than safety and moral factors exacerbate the situation. Major lessons to be learnt are 1) the effectiveness of disaster management should be restudied in all hazardous countries; 2) the importance of the high-Tech early-warning systems in reducing risk; 3) Reconsidering of extreme values expected/possible hazard and risk levels is necessary; 4) Morality and might be taken as an important factor in disaster management; 5) Sustainable development should be taken as the basis for reconstruction after disaster.